Development of Hot Equal Channel Angular Processing (ECAP) Consolidation Technique in the Production of Boron Carbide(B4C)-Reinforced Aluminium Chip (AA6061)-Based Composite - Sami Al-Alimi; Mohd Amri Lajis; Shazarel Shamsudin; Nur Kamilah Yusuf; Boon Loong Chan; Djamal Hissein Didane; Mohammed H. Rady; Huda M. Sabbar; Munthader S. Msebawi (International Journal of Renewable Energy Development, 2021)
The production of metal matrix composites (MMCs) through recycled materials is a cost-saving process. However, the improvement of the mechanical and physical properties is another challenge to be concerned. In this study, recycled aluminium 6061 (AA6061) chips reinforced with different volumetric fractions of boron carbide (B4C) were produced through hot equal channel angular processing (ECAP). Response surface methodology (RSM) was carried out to investigate the dependent response (compressive strength) with independent parameters such as different volumetric fractions (5-15%) of added contents of B4C and  preheating temperature (450 – 550°C). Also, the number of passes were examined to check the effect on the mechanical and physical properties of the developed recycled AA6061/B4C composite. The results show that maximum compressive strength and hardness of recycled AA6061/B4C were 59.2 MPa and 69 HV respectively at 5% of B4C contents. Likewise, the density and number of pores increased, which were confirmed through scanning electron microscope (SEM) and atomic force microscopes (AFM) analysis. However, the number of passes enhanced the mechanical and physical properties of the recycled AA6061/B4C composite. Therefore, the maximum compressive strength and hardness achieved were 158 MPa and 74.95 HV for the 4th pass. Moreover, the physical properties of recycled AA6061/B4C composite become denser of 2.62 g/cm3 at the 1st pass and 2.67 g/cm3 for the 4th pass. Thus, it can be concluded that the B4C volumetric fraction and number of passes have a significant effect on recycled AA6061 chips.